Advances in Austrian economics. Vol. 2, pt. 2 - Koppl, Roger; Boettke, Peter; Rizzo, Mario (Emerald, 1995)
This second volume in the series Advances in Austrian Economics is divided into three parts. The first part is a series of essays in honor of Israel M. Kirzner, co-editor of the first volume in the series, the second part contains books reviews, and the third, a bibliography.
Keywords: Austrian school of economics.; elektronické knihy; electronic books